Skylines and other dominance-based queries - Papadopoulos, Apostolos N.; Tiakas, Eleftherios; Tzouramanis, Theodoros; Georgiadis, Nikolaos; Manolopoulos, Yannis 1957- (Morgan & Claypool Publishers, 2020)
1. Introduction -- 1.1. Objects and attributes -- 1.2. The concept of dominance -- 1.3. Best points -- 1.4. Book roadmap -- 1.5. Summary
Part of: Synthesis digital library of engineering and computer science
Includes bibliographical references (pages 113-130) and index
Keywords: Abfrageverarbeitung; Datenbanksystem; Querying (Computer science); Computer algorithms; Decision making / Data processing; Decision making; Data processing